Spiritualitas Dan Resiliency Of Self Efficacy Pada Pekerja Seks Komersil Melalui Psikodrama - Sri Kandariyah Nawangsih; Hermiana Vereswati; Nurul Lis Maulidda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In August 2019, the Semarang City Government closed the Sunan Kuning localization. This community service aims to see a picture of spiritualism and resilience of self-efficacy in former female commercial sex workers who live in the Sunan Kuning area of ​​Semarang. Methods of using psychodrama. The participant profile shows that the majority are elementary school graduates at 53.8%, marital status is divorced at 61.5%. Observation results show that economic factors, loss of income as a prostitute, large number of children, separation from friends are the causes of sadness, anger, stress and feelings of fear after the closure of localization. Overall, psychodrama activities give rise to better thoughts and feelings, including being able to express sadness, a means of catharsis and the spirit of continuing entrepreneurship and becoming a better person.